PENINGKATAN KEMAMPUAN KEPALA TK SEBAGAI SUPERVISOR MELALUI SKILL TRAINNING FOR THE JOB DINAS PENDIDIKAN KECAMATAN BULUTAHUN 2015 - Subarjo . (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
Supervisory Unit Kindergarten of sub-district Bulu Abstrak Educational Research Office is done at the Sub-District Education Officein?é?á Bulu,District : Temanggung, the subject and object of study is a number of 15 Head of kindergarten. The study aims to determine the increase skill/capacity of kindergarten as Supervisor, at the District Education Office of Bulu, and to knowthe?é?á activity and?é?á spirit of the Head Office of Head of Kindergarten at The Educational Unit, Sub-District Bulu during joining the Skill Training For The Job. The research analysis uses comperative discriptive?é?á and procentage discriptive. Results of the study showed that the knowledge aspects and concepts of supervision, head of the kindergarten gained an average score of 46.66, or (D) the category of "less", while the head of the TK ability as supervisor obtained an average score of 30.65, or (D), the category of "Less" The results of this study, after training with two cyclus increased. Aspects of knowledge and insight of Kindergarten Head about academical supervisi and managerial increased with classical completeness 100%, with an average score of 86 or A, the category of "Very Good". Attitude aspects and activity increased with classical completeness 95%, average scores average 79.71 or (B), the category of "Good". While theaspect?é?á of Kindergarten Head as a Supervisor?é?á increased with classical completeness by 94.07%, with an average score, 82.39, the category of "Good" .Based on this results of this study, the purpose of this study was to knowthe upgrades of?é?á kindergarten Head as a supervisor and activities / spirit of the heads of kindergartens in Tasked Implementing Unit ( UPT ) Educational Authorities in Sub-District Bulu by training :Skill Training For The Job reached. Key words: Ability TK Head, Supervisor, Skill Trainninng For The job.